SISTEM PENGHITUNG JUMLAH PESERTA SEMINAR BERBASIS IOT - Joni Warta; Kusdarnowo Hantoro; Asep Ramdhani Mahbub (JSI (Jurnal Sistem Informasi) Universitas Suryadarma, 2021)
AbstractSeminar activities in a building in general still use manual in recording to know the number of seminar participants who attended.Â  Although the seminar applicants are still uncertain whether they will come for the seminar in the building or not, so the number of seminar applicants is not necessarily the same as the number of participants entering the building. The calculation of the number of participants can also be used to close the entrance of the building if the number of seminar participants is in accordance with the participants who signed up, so as to ensure the number of seminar participants who arrived late. From the results of the analysis and discussion that has been obtained, with the implementation of Arduino and ESP32 CAM and PIR, the system of counting the number of seminar participants using Telegram, the number of seminar participants who attended in real time and online and with the storage of data and photos of participants automatically stored in the memory of mobile phones, facilitate seminar participants and committees in document making or verifying the presence of seminar participants.Â Keywords: Registration, Attended, Seminar, Arduino, Telegram.